Assessing and managing problematic sexual interests : a practitioner's guide - Akerman, Geraldine (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Assessing and Managing Problematic Sexual Interests: A Practitioner's Guide provides a thorough review of atypical sexual interests and offers various ways through which they can be measured and controlled, including compassion-focused and psychoanalytic approaches. This unique guide presents a detailed analysis of deviant sexual interest. The first section, "Assessment," overviews the range of sexual interests and fantasies in men and women. The second section, "Management," investigates the cutting-edge tools, approaches, interventions, and treatment advances used in a variety of settings to control deviant sexual interest. Throughout, Assessing and Managing Problematic Sexual Interests offers necessary perspectives and emerging research from international experts at the forefront of this field. With a thorough assessment of current research and a critical overview of treatment advances for problematic sexual interests, Assessing and Managing Problematic Sexual Interests is an essential resource for clinical and forensic psychologists, probation officers, academics, students working in the field, and members of allied professional fields"--
OCLC-licensed vendor bibliographic record.
Keywords: Paraphilias -- Psychological aspects; Fetishism (Sexual behavior); Psychoanalysis; PSYCHOLOGY / General; PSYCHOLOGY / Forensic Psychology